Research on Low Carbon Information Disclosure and Low Carbon Transition Efficiency of Listed Power Generation Companies - ZHAO Changhong; ZHANG Lilin; SHAO Yunshu; YUAN Jiahai; DENG Yilu (发电技术)
ObjectivesAfter the “dual-carbon” goal was put forward, the electric power industry has accelerated the low-carbon transition, and power generation enterprises have incorporated low-carbon transition into their corporate development plans and strategies. In order to explore the consistency between low-carbon transformation goal commitments and implementation results, important factors influencing low-carbon transformation efficiency were explored, and the intrinsic connection between textual information and low-carbon transformation efficiency was studied.MethodsThis paper took 31 listed power generation companies as the research object from 2016 to 2022, and adopted the text analysis technique to construct a measurement index of the level of textual disclosure of low-carbon transition, and empirically examined the relationship between textual disclosure and the efficiency of low-carbon transition by using the panel regression model with bidirectional fixed effects.ResultsThe higher the level of textual information disclosure of low-carbon transition of listed power generation companies is, the lower the carbon emission intensity is, the better the environmental performance is, i.e., the higher the efficiency of the transition is, and the more consistent the company’s “words” and “actions” are. In addition, in companies with higher quality of accounting information disclosure and lower thermal power installed capacity, the effect of the disclosure level of low-carbon transition text on low-carbon transition efficiency is more significant.ConclusionsThe listed power generation companies should improve the quality of textual information disclosure of low-carbon transition, and play the role of supervision and management of annual report textual information to promote the development of low-carbon transition, and realize the consistency between textual information disclosure and transition efficiency.